Adipokines: Potential Therapeutic Targets for Vascular Dysfunction in Type II Diabetes Mellitus and Obesity - Mostafa Wanees Ahmed El husseny; Mediana Mamdouh; Sara Shaban; Abdelrahman Ibrahim Abushouk; Marwa Mostafa Mohamed Zaki; Osama M. Ahmed; Mohamed M. Abdel-Daim (Journal of Diabetes Research)
Adipokines are bioactive molecules that regulate several physiological functions such as energy balance, insulin sensitization, appetite regulation, inflammatory response, and vascular homeostasis. They include proinflammatory cytokines such as adipocyte fatty acid binding protein (A-FABP) and anti-inflammatory cytokines such as adiponectin, as well as vasodilator and vasoconstrictor molecules. In obesity and type II diabetes mellitus (DM), insulin resistance causes impairment of the endocrine function of the perivascular adipose tissue, an imbalance in the secretion of vasoconstrictor and vasodilator molecules, and an increased production of reactive oxygen species. Recent studies have shown that targeting plasma levels of adipokines or the expression of their receptors can increase insulin sensitivity, improve vascular function, and reduce the risk of cardiovascular morbidity and mortality. Several reviews have discussed the potential of adipokines as therapeutic targets for type II DM and obesity; however, this review is the first to focus on their therapeutic potential for vascular dysfunction in type II DM and obesity.